Ectopic breast carcinoma presenting as sebaceous cyst left axilla. Issue 1 (24th January 2019) - Jalali, Uzma; Dhebri, Alhad; Karip, Eszter; Hunt, Roger
Abstract : A 43-year-old woman with a positive family history of breast cancer presented with a painless lump in her left axilla for 2 years. Clinical diagnosis was a left axillary sebaceous cyst as the lump was inseparable from the skin. The lesion was excised under local anaesthesia and reported as breast tissue widely infiltrated by an invasive ductal carcinoma (grade 2). The malignancy was not involving the epidermis but <1 mm away from deeper margins. Re-excision of the deeper tissue with an axillary sentinel lymph nodes biopsy was performed and deep margins were reported to be tumour-free with no nodal involvement.